PERMASALAHAN HUKUM DALAM PENGEMBANGAN ILMU HUKUM DI INDONESIA (PENTINGNYA REFORMASI HUKUM TERKAIT DENGAN PERMASALAHAN HUKUM) - Ismansyah, Ismansyah (Jurnal Demokrasi, 2010)
Law is a complex system. Linkages between the elements can not be separated. Law is not just the law, the law is not always a command of the State authorities. Law is the result of social forces and means of social control. Legal basically non-sterile from social subsystem. Politics often intervene on the act and the implementation of the law. law can be viewed and studied from various angles. Law as a value, then reviewed by the legal and political filasafat law. Kaedah studied by law as legal science. law as a learned behavior by the Sociology of Law, legal anthropology and psychology of law. The inability of law in addressing social problems outside the law will result in the authority of the law itself. Keywords: law, legal problems, the development of legal science, legal reform